Public private partnership in ASEAN countries: The role of investment climate - Emirullah, Chandra (2013)
The countries in South East Asia have achieved remarkable performance in economic development during the last decade. 'The economic growth of several members of ASEAN such as Singapore, Malaysia, Thailand, Indonesia, Vietnam, and lately the Philippines, are among the highest in the world.However, the lack of infrastructure is becoming more and more a critical constraint in furthering the expansion of these economies especially in the latter five countries. The pressuring need for infrastructure development combined with the lack of the ability of the governments to finance it has led many developing countries including these ASEAN countries to adopt Public Private Partnership (PPP) Program to help them cope with the infrastructure problem. While some countries such as India, South Korea, and China, have been successful in implementing this program,the ASEAN countries' record is not very impressive.Some countries such as Singapore and Malaysia have relatively good results, but the others are still lagging behind.This study intends to look into the role of investment climate in affecting PPP performance in the big six of the ASEAN economies, which are in this case, Indonesia, Malaysia, 'Thailand, the Philippines, Vietnam and Singapore. The analysis will be based on data from World Bank Indicator data base and Panel Data Model.With this approach, it is hoped that the critical factors that influence the achievement of PPP can be found out.